2018
DOI: 10.17267/2238-2720revbahianaodonto.v9i1.1802
|View full text |Cite
|
Sign up to set email alerts
|

Biomodulatory Potential of Low-Level Laser on Neoangiogenesis and Remodeling Tissue. A Literature Review

Abstract: Introduction: In recent years, cellular biostimulation induced by low-level laser therapy has been widely studied. Among some of the processes stimulated by low-level laser are cell cycle, phenotypic modulation as well as vascular changes, such as vasodilation and neoangiogenesis. The increased number of new blood vessels accelerates inflammation, and also increases wound healing. Neoangiogenesis is still an important process of tissue repair, since it always precedes collagen synthesis and matrix extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…All the procedures were in accordance with Fortuna et al 4 Anesthesia was administered intraperitoneally with a combination of ketamine (50 mg/kg) and xylazine (10 mg/ kg) at a dose of 0.2 mL/100 g of body weight. Then, the animals were shaved on the dorsal region and an iodophor was used as a sanitizer (Biochemistry, Rio de Janeiro, Brazil).…”
Section: Experimental Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the procedures were in accordance with Fortuna et al 4 Anesthesia was administered intraperitoneally with a combination of ketamine (50 mg/kg) and xylazine (10 mg/ kg) at a dose of 0.2 mL/100 g of body weight. Then, the animals were shaved on the dorsal region and an iodophor was used as a sanitizer (Biochemistry, Rio de Janeiro, Brazil).…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Recent studies have shown that laser photobiomodulation (LPBM) accelerates the acute phase of inflammation, stimulates cell proliferation, increases the contraction of skin wounds, and accelerates re-epithelialization. [1][2][3][4] Does LPBM also modulate the later phases of wound healing? Although few studies have investigated this matter, 1,5 the answer to this question is still unclear because the duration of the benefits derived from LPBM can be perpetuated in irradiated tissues.…”
Section: Introductionmentioning
confidence: 99%